(untitled) (Journal of the College of Languages (JCL), 2024)
This work intends to illustrate the methods of using the authentic literary text in the process of spreading Italian, especially in Baghdad where there is a strong propensity to learn the Italian language. The concept of the language that arises from literature is an idea closely linked to the mentality of the Arab learner towards Italian culture: an idea also created by the first Arabisations of literary texts in the early years of the previous century. The research was carried out in Baghdad by two researchers, an Italianist from Baghdad and an Italian mother language linguist, with the aim of bringing together the two sectors in favor of the diffusion of the Italian language. The study also aims to clarify the models from Italian literature most welcomed by those who study Italian in Iraq. In addition to making clear the conceptual phases of what is meant by a literary text in the process of dissemination of a language, and how to expand the literary canon by referring to the corpus of the language of the different genres of Italian literature. Il presente lavoro intende illustrare le modalità d’impiego del testo letterario autentico nel processo di diffusione dell’italiano, soprattutto a Baghdad dove si sta assistendo ad una forte propensione all’apprendimento della lingua italiana. Il concetto della lingua che nasce dalla letteratura è un’idea molto legata alla mentalità dell’apprendente arabo nei confronti della cultura italiana: idea creata anche dalle prime arabizzazioni dei testi letterari ai primi anni del secolo precedente. La ricerca è stata eseguita a Baghdad da due ricercatori, un italianista di Baghdad ed un linguista italiano, allo scopo di riunire i due settori a favore della diffusione della lingua italiana. Lo studio vorrà anche chiarire i modelli dalla letteratura italiana più accolti da chi studia l’italiano in Iraq. Oltre a rendere evidenti le fasi concettuali di che cosa si intende per testo letterario nella disseminazione di una lingua, e come ampliare il canone letterario facendo riferimento al corpus del linguaggio dei diversi generi della letteratura italiana. Received on 26/7/2023 Accepted on 20/8/2023 Published on 2/1/2024